Personalized Hydration Strategy Attenuates the Rise in Heart Rate and in Skin Temperature Without Altering Cycling Capacity in the Heat - de Melo-Marins, Denise; Souza-Silva, Ana Angélica; da Silva-Santos, Gabriel Lucas Leite; Freire-Júnior, Francisco de Assis; Lee, Jason Kai Wei; Laitano, Orlando (Frontiers in Nutrition, 2018)
The optimal hydration plan [i.e., drink to thirst, ad libitum (ADL), or personalized plan] to be adopted during exercise in recreational athletes has recently been a matter of debate and, due to conflicting results, consensus does not exist. In the present investigation, we tested whether a personalized hydration strategy based on sweat rate would affect cardiovascular and thermoregulatory responses and exercise capacity in the heat. Eleven recreational male cyclists underwent two familiarization cycling sessions in the heat (34°C, 40% RH) where sweat rate was also determined. A fan was used to enhance sweat evaporation. Participants then performed three randomized time-to-exhaustion (TTE) trials in the heat with different hydration strategies: personalized volume (PVO), where water was consumed, based on individual sweat rate, every 10 min; ADL, where free access to water was allowed; and a control (CON) trial with no fluids. Blood osmolality and urine-specific gravity were measured before each trial. Heart rate (HR), rectal, and skin temperatures were monitored throughout trials. Time to exhaustion at 70% of maximal workload was used to define exercise capacity in the heat, which was similar in all trials (p = 0.801). Body mass decreased after ADL (p = 0.008) and CON (p < 0.001) and was maintained in PVO trials (p = 0.171). Participants consumed 0 ml in CON, 166 ± 167 ml in ADL, and 1,080 ± 166 ml in PVO trials. The increase in mean body temperature was similar among trials despite a lower increase in skin temperature during PVO trial in comparison with CON (2.1 ± 0.6 vs. 2.9 ± 0.5°C, p = 0.0038). HR was lower toward the end of TTE in PVO (162 ± 8 bpm) in comparison with ADL (168 ± 12 bpm) and CON (167 ± 10 bpm), p < 0.001. In conclusion, a personalized hydration strategy can reduce HR during a moderate to high intensity exercise session in the heat and halt the increase in skin temperature. Despite these advantages, cycling capacity in the heat remained unchanged.